ECO-PRECARITY: A SOCIO-ECOLOGICAL STUDY OF THE COMMUNITY IN ARTISANAL MINING IN BANJARBARU, SOUTH KALIMANTAN - Laila Azkia; Toetik Koesbardiati (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
This study examines eco-precarity as a condition of socio-ecological vulnerability experienced by the diamond mining community in Cempaka District, Banjarbaru City. The main objective of this study is to understand how societies deal with ecological and economic uncertainty in their daily lives. Using qualitative approaches and phenomenological strategies, data was collected through field observations and in-depth interviews with miners, machine owners, and local policy makers. The results show that societies are highly dependent on depleted natural resources, while expansive cultures and profit-sharing economies reinforce the cycle of vulnerability. Severe environmental damage, low levels of education, and a change-resistant mindset reinforce eco-precarity as a structural condition that is inherited between generations. Identity as a harvester is considered a destiny, making mining work not just an economic activity, but part of culture. These findings confirm that eco-precarity is not only triggered by ecological crises, but also by social and cultural structures that limit people's adaptive abilities. Therefore, development interventions need to consider a socio-ecological approach that is just, especially in the context of small-scale small-scale smallholder mining.